Răspuns:
[tex]\sqrt{3} - \sqrt{2}[/tex]
Explicație pas cu pas:
[tex](\frac{2}{\sqrt{2} } - \frac{3}{\sqrt{3} } )*\sqrt{6} + (\frac{3}{\sqrt{18} } - \frac{10}{\sqrt{75} } )(-\sqrt{6} )[/tex]
[tex]= (\frac{2\sqrt{3} - 3\sqrt{2} }{\sqrt{6} } )*\sqrt{6} + (\frac{3}{3\sqrt{2} } - \frac{10}{5\sqrt{3} } )(-\sqrt{6} )[/tex]
[tex]= 2\sqrt{3} - 3\sqrt{2} +( \frac{1}{\sqrt{2} } - \frac{2}{\sqrt{3} } )(-\sqrt{6} )[/tex]
[tex]= 2\sqrt{3} - 3\sqrt{2} + \frac{\sqrt{3} - 2\sqrt{2} }{\sqrt{6} } (-\sqrt{6} )[/tex]
[tex]= 2\sqrt{3} - 3\sqrt{2} - \sqrt{3} + 2\sqrt{2}[/tex]
[tex]= \sqrt{3} - \sqrt{2}[/tex]